Optimization of Industrial Development Based on Local Potential in Tanjungpinang - Nurhasanah; Ezky Tiyasiningsih (Journal of Research in Business, Economics, and Education, 2023)
Industrial development based on local resources is part of local economic development. This is not something new, but the concept of local economic development and its implementation techniques continue to evolve. In general, regional or local economic development is essentially an effort to strengthen local economic competitiveness for regional economic development and the accumulation of these activities will have a major impact on the development of national economic competitiveness and strengthening national economic competitiveness. Local Economic Development itself is essentially "A process when actors within a community, whether city, regional area or major cities, namely government, private sector and community, work collectively to create economic development conditions and better generation growth. The local-based industrial sector plays a role as a leading sector that can stimulate and lift the development of other sectors in the city of Tanjungpinang. With this study, it is certainly expected to change the GRDP data of Tanjungpinang City where so far the industrial sectors have not become the main sectors driving the Tanjungpinang City economy. Based on the GRDP data At Current Prices by business field in Tanjungpinang City in 2017, the industrial sector is in the fourth rank with a value of 1198.38 billion rupiah. The first rank is the Construction Sector with a value of 5670.95 billion rupiah. The second order is the trade sector with a value of 4661.93 billion rupiah. The third order is the government administration sector with a value of 1825.5 billion rupiah (BPS Tanjungpinang City, 2020).